Women and Leadership in the European Union 2022
DOI: 10.1093/oso/9780192896216.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Leadership in the European Parliament’s Political Groups

Abstract: The chapter analyzes how leadership continues to be gendered in the European Parliament (EP), failing to provide a level playing field for MEPs. It focuses on the leadership positions provided by the political groups of the Parliament. Political groups have grown in importance alongside the institutional development of the EP, and leadership positions within them encompass those responsible for political, policy, and administrative leadership. This chapter analyzes political leadership in terms of political gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Political groups have notably different selection procedures for these positions, combining both formal rules and procedures and informal norms. Formal rules in political group statutes can make for open and transparent selection procedures and enhance equality and democracy, while informal norms-prominent in the radical right groups-induce more opaque and less democratic processes (Kantola & Miller, 2022;see Ahrens & Kantola in this volume).…”
Section: New Inroads Into the Study Of Political Groupsmentioning
confidence: 99%
“…Political groups have notably different selection procedures for these positions, combining both formal rules and procedures and informal norms. Formal rules in political group statutes can make for open and transparent selection procedures and enhance equality and democracy, while informal norms-prominent in the radical right groups-induce more opaque and less democratic processes (Kantola & Miller, 2022;see Ahrens & Kantola in this volume).…”
Section: New Inroads Into the Study Of Political Groupsmentioning
confidence: 99%
“…Once in office, women's political careers and the quality of their representative work are shaped by the gendered inequalities in parliaments (Erikson & Verge, 2022). In the EP, extant research shows that, first, gendered leadership structures and expectations have led to women being more equally represented in policy leadership (in committee chair and coordinator positions) than in political (political group leaders) or administrative (secretaries general) leadership positions (Kantola & Miller, 2022). Second, patterns of gender-based discrimination have been identified.…”
Section: Researching Gendered Inequalities and Gender Equality Practi...mentioning
confidence: 99%
“…The Greens/EFA group had two women serving as committee chairs, while at the GUE/NGL, it was one man. The coordinator positions were equally divided (Kantola & Miller, 2022).…”
Section: Gender Equality As a Fundamental Principle: Greens/efa And G...mentioning
confidence: 99%
See 1 more Smart Citation
“…The research material also reported instances where the Bureau tried to silence MeTooEP by informally calling the organizers of an event, in which MeTooEP was invited to speak, in order to block their intervention (S&D staff 8:12; S&D staff 2:33), in view of protecting the Parliament's notoriety (Author, 2020). As a result, the Secretariat and Bureau, both gendered institutional bodies (Kantola and Miller, 2022), constrained MeTooEP both passively -'inertia'and activelyby silencing the campaign. (Ahrens, 2018) Lastly, elected Members of the European Parliament (MEPs) and their political groups were two key institutional bodies for MeTooEP as they helped and empowered it.…”
Section: A Campaign Constrained By Its Institutional Contextmentioning
confidence: 99%